Translational Potential of Therapeutics Targeting Regulatory Myeloid Cells in Tuberculosis - du Plessis, Nelita; Kotze, Leigh A.; Leukes, Vinzeigh; Walzl, Gerhard (Frontiers in Cellular and Infection Microbiology, 2018)
Despite recent advances in tuberculosis (TB) drug development and availability, successful antibiotic treatment is challenged by the parallel development of antimicrobial resistance. As a result, new approaches toward improving TB treatment have been proposed in an attempt to reduce the high TB morbidity and mortality rates. Host-directed therapies (HDTs), designed to modulate host immune components, provide an alternative approach for improving treatment outcome in both non-communicable and infectious diseases. Many candidate immunotherapeutics, designed to target regulatory myeloid immune components in cancer, have so far proven to be of value as repurposed HDT in TB. Several of these studies do however lack detailed description of the mechanism or host pathway affected by TB HDT treatment. In this review, we present an argument for greater appreciation of the role of regulatory myeloid cells, such as myeloid-derived suppressor cells (MDSC), as potential targets for the development of candidate TB HDT compounds. We discuss the role of MDSC in the context of Mycobacterium tuberculosis infection and disease, focussing primarily on their specific cellular functions and highlight the impact of HDTs on MDSC frequency and function.